2011
DOI: 10.3109/17435390.2011.587903
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide nanoparticles exhibit genotoxicity and impair DNA repair activity in A549 cells

Abstract: Titanium dioxide nanoparticles (TiO(2)-NPs) are produced in large quantities, raising concerns about their impact for human health. The aim of this study was to deeply characterize TiO(2)-NPs genotoxic potential to lung cells, and to link genotoxicity to physicochemical characteristics, e.g., size, specific surface area, crystalline phase. A549 cells were exposed to a panel of TiO(2)-NPs with diameters ranging from 12 to 140 nm, either anatase or rutile. A set of complementary techniques (comet and micronucleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
167
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(193 citation statements)
references
References 41 publications
20
167
2
4
Order By: Relevance
“…P53 is a central player in the DNA damage response. Its activation can be directly caused by the DNA damage that we and others previously reported in cells exposed to TiO 2 -NPs either acutely [4,21,48] or chronically [13] and which is characterized by oxidative lesions and DNA strand breaks, including double-strand breaks that may result from the duplication of cells with replication fork blockade [48]. It may also be linked to the impaired glucose metabolism that our proteomics results reveal; indeed p53 is also activated upon cell starvation and metabolic stress [49].…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 2 more Smart Citations
“…P53 is a central player in the DNA damage response. Its activation can be directly caused by the DNA damage that we and others previously reported in cells exposed to TiO 2 -NPs either acutely [4,21,48] or chronically [13] and which is characterized by oxidative lesions and DNA strand breaks, including double-strand breaks that may result from the duplication of cells with replication fork blockade [48]. It may also be linked to the impaired glucose metabolism that our proteomics results reveal; indeed p53 is also activated upon cell starvation and metabolic stress [49].…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…The energy delivered by our sonicator was measured, amplitude of 28% corresponds to 16.7 W [20]. The physico-chemical properties of these TiO 2 -NPs have already been described in our previous articles [19,21]. Briefly, their crystalline structure is mixed anatase/rutile (86%/14%) [21], their primary diameter is 25±7 nm and their specific surface area is 46±1 m²/g [19].…”
Section: Nanoparticles Dispersion and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Titanium dioxide nanoparticles (TiO 2 -NP) are widely used in the manufacture of paints, paper, plastic, laminate flooring materials, food coloring and cosmetics (Jugan et al, 2012). Due to their photocatalytic properties these nanoparticles are also used in wastewater and as environmental disinfectants (Cho et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…They also observed that the DNA damage caused by nano-TiO 2 was single-strand breaks and 8-oxodGuo, but not double-strand breaks or chromosomal breaks or losses. Furthermore, the nanoparticles inactivated both nucleotide excision repair abilities (NER) and base excision repair (BER) pathways leading to the losing of cell ability to repair the damaged DNA (Jugan et al 2012). Two more recent papers presented similar conclusion.…”
Section: Toxicity Of Nano-tio 2 On Respiratory Systemmentioning
confidence: 59%